(untitled) (Revista Nacional de Odontología, 2019)
Introduction: The oral health care of children in early childhood is mediated by the knowledge and daily practices of responsible adults. This work attempts to analyze the knowledge and practices of adults responsible for oral care of children between 3 and 5 years, linked to the Las Golondrinas Foundation, Medellin, Colombia. Materials y methods: A qualitative case study, 27 interviews were conducted with significant adults related to the oral care of children linked to the institution. Results and conclusions: The adults reported their ease of access to information from various sources that, together with their motivation and experiences, has allowed them to build knowledge and adopt oral care practices in which they find new possibilities for care actions. As health educators, it is necessary to transcend disciplinary actions to contribute to the construction of protective processes, in which hygiene elements and techniques are integrated into contextual practices that contribute to different aspects of parenting, taking care of children in their different states of being.